A comparative study between desflurane and sevoflurane in recovery time and recovery characteristics on patients for elective orthopedic procedure - Alias, Raja Liza Raja (2006)
The safety of anaesthetic recovery is closely related to the speed of which the patient reaches a state of stable circulation, respiration and well maintained reflexes. Apart from the risk of surgical complications, the risk of residual anaesthetic effects, are the reason for keeping patients in a highly staffed, and high surveillance recovery unit. With the new rapidly eliminated inhalational anaesthetic agent, such as destlurane, having low blood gas solubility coefficient (0.42), it is supposed to offer a rapid recovery. The socalled fast-track concept means that the patient is so well recovered when he leaves the operating theatre that tbe recovery unit may be by-passed without any risk for the patient. A randomized single blinded prospective study was conducted in Hospital Universiti Sains Malaysia from June 2004 to Jooe 2005 involving a total of 60 ASA I patients planned fur elective orthopedic procedures with duration of surgery less then 2 hours. The patients were allocated into 2 equally numbered groups, desflurane (n=30) and sevoflurane (n=30). The objectives of the study were to compare the effect of desflurane versus sevoflurane as inhalational agent for maintenance, on recovery time and side effects. All patients were induced with intravenous fentanyl, propofol and atracurium. Intraoperatively, either desflurane 6% or sevoflurane 2% (which are equivalent to lMAC of both agents in 1000.4 oxygen) was used together with 30010 oxygen and 700,4, nitrous oxide. Atracmimn infusion was used as a muscle relaxant and fentanyl was given for analgesia. Hemodynamic parameters (blood pressure and heart rate) were recorded on arrival, pre ... intubation, post-intubation and every l 0 minutes until the end of the surgery. Bispectral index scale (BIS) was used to monitor anaesthetic depth. During emergence, stimulation of patients was limited to verbal encouragement to open eyes with a tap on the shoulder at 10 seconds interval. Time was recorded from discontinuation of anaesthetic until patients opened their eyes and obeyed simple commands. The changes in BIS values with time were recorded as the inhalational agent was discontinued. At the same time, patients were observed for any complications during emergence and at the recovery room. From this study, there was significant difference between desfturane and sevotlurane in tenns of recovery time, which included time to open eyes (7 .2l:r 1.82 minutes, for destlurane versus 12.55±2.70 minutes, for sevoflurane with p < 0.001) and time to obey command (8.33±1.77 minutes, for desflurane versus 13.52±2.65 for sevotlurane with p < 0.001 ), with the duration of operation within 2 hours. The changes in BIS values with time showed significance difference between the groups, which was ~ with desfluranegroups. However, there was no significant difference in term of hemodynamic parameters between the groups. There were 5 (16. 7%) incidence of complications during emergence/recovery in patients who received sevoflurane. However it was not statistically significant. In summary, this study showed that desflurane has a faster recovery time with similar hemodynamic and side effects as compared to sevoflurane.